2017
DOI: 10.1007/978-3-319-56608-5_21
|View full text |Cite
|
Sign up to set email alerts
|

E-Government and the Digital Divide: A Study of English-as-a-Second-Language Users’ Information Behaviour

Abstract: Internet-based technologies are increasingly used by organisations and governments to offer services to consumers and the public in a quick and efficient manner, removing the need for face-to-face conversations and human advisors. Despite their obvious benefits for most users, these online systems may present barriers of access to certain groups in society which may lead to information poverty.In this study we consider the information behaviour of ten ESL (English as a Second Language) participants as they con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…This was echoed by native participant B1, who explained that assistance would be used (in other settings) to complete queries to save time. A comparison of queries, classified based on the definitions of Chu et al [8],found that there were no differences in the distribution of queries submitted across both groups, with new queries and reformulations (66.43% for non-natives and 68.91%) making up the majority of submitted queries, despite being contrary to the initial study [8], this has been identified previously [5].…”
Section: Behavioursmentioning
confidence: 71%
See 3 more Smart Citations
“…This was echoed by native participant B1, who explained that assistance would be used (in other settings) to complete queries to save time. A comparison of queries, classified based on the definitions of Chu et al [8],found that there were no differences in the distribution of queries submitted across both groups, with new queries and reformulations (66.43% for non-natives and 68.91%) making up the majority of submitted queries, despite being contrary to the initial study [8], this has been identified previously [5].…”
Section: Behavioursmentioning
confidence: 71%
“…This raises questions about users whose native language is not English, and the barriers they face if governmental services are solely accessible on-line. Brazier and Harvey [5] studied the search behaviours and performance of ESL users when given search tasks that new immigrants to a country might need to perform and found that, while most users were very confident of their English language searching abilities, they did not perform very well.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Several investigators have organized the effects of language skills on monitoring search behavior of clients with many other languages as native. 15 Furthermore, Brazier and Harvey 16 employed the effect on language skills of investigation attitude. Now, four search operations have been created and calculated the pre and post search information for finding the process reputation.…”
Section: Related Workmentioning
confidence: 99%